Familial Responses to Financial Instability, "It's All Your Fault": Predictors and Implications of Blame in Couples Under Economic Strain, 2009 (United States) - Diamond, Lisa ([Verlag nicht ermittelbar], 2010)
On behalf of the National Center for Family and Marriage Research, Knowledge Networks conducted a survey about financial management behaviors among 600 opposite sex married or cohabiting couples. Both partners were invited to participate in the survey at the same time. The data collection began on August 18, 2009, and continued through August 24, 2009. A total of 2,495 panelists were invited to participate in the survey. Among the 1,595 (64%) who responded to the survey, 1,264 (51%) were eligible and completed the questionnaire. Measures included variables on partner/relationship satisfaction, financial problems, and blame.